How music works : the science and psychology of beautiful sounds, from Beethoven to the Beatles and beyond - Powell, John, 1955- (New York : Little, Brown and Company, 2011)
John Powell, a scientist and musician, answers questions about harmony, timbre, keys, chords, loudness, musical composition, and many more in this intriguing and original guide to acoustics.
CD. How to get different sounds from a guitar string -- Can you guess what this instrument is? -- Why some notes clash and others get along together -- Different ways to accompany a tune -- Ancient and modern scales -- 3,000-year-old music : ancient harp tuning -- The horrible out-of-tune bamboo whistle -- Confident majors and emotional minors -- How to bring tears to the eyes of the audience -- The magnificent drinking-straw oboe.
Book is accompanied by one CD, entitled'How music works' bearing the same call number and available at Bahagian Koleksi Media.
Includes bibliographical references (p. [255]-257) and index.
Keywords: Music -- Acoustics and physics; Music -- Psychological aspects